(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
After considering the decision of the shareholding company to buy part of its shares as one of the decisions surrounded by distrust in terms of its theoretical departure from the basic purposes of the company, not to mention the possibility of prejudice to it’s the company’s capital, Is now an integral part of the policy of the major international companies, because of the acquisition of these privileges to enable the shareholding companies to cope with market fluctuations and external control tools that may resort to competitors for the purpose of acquisition, As well as the possibility of using them in the context of their investment policies and in the framework of activating the reward and incentive systems for their employees, which made the study of the mechanism of implementation in the stock market is an urgent need as it may contribute to removing the ambiguity of both companies or investors and thus reduce the possibility of transformation To a fraudulent tool.